Konsekuensi Hukum Dan Tanggung Jawab Notaris Atas Pelanggaran Kode Etik: Analisis Yuridis Normatif - Kusuma, Irene; Indratirini (Journal Evidence Of Law, 2025)
The notary profession as a public official has a strategic role in providing legal certainty through the creation of authentic deeds, but the phenomenon of code of ethics violations in practice creates complex problems regarding the legal consequences that can be caused. This study analyzes the causal relationship between violations of the notary code of ethics and legal consequences using normative juridical methods with a descriptive-analytical qualitative approach. Research data sources use primary legal materials in the form of laws and regulations, notary code of ethics, and court decisions, as well as secondary legal materials in the form of relevant legal literature. Data analysis was carried out using legal hermeneutic techniques and comparative analysis with notarial systems in other countries. The results show that the notary code of ethics has a position as a binding legal norm based on explicit recognition in the Notary Position Law, with a classification of violations that can cause legal consequences in the form of administrative, civil, and criminal liability. The legal accountability mechanism involves the Notary Supervisory Council, the Notary Honorary Council, and the judicial system with gradations of sanctions adjusted to the level of violation. However, the effectiveness of sanctions has not been optimal in providing deterrent, restorative, and educational effects. The study recommends the need to revise the code of ethics to provide more measurable definitions, reform the supervisory structure by increasing independence and transparency, and strengthen the sanctions system that applies the principle of restorative justice to increase accountability and public trust in the notary profession.